2022
DOI: 10.12688/f1000research.74645.1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of sex differences for COVID-19 infection, hospitalisation, severe disease, intensive care unit (ICU) admission and death: a meta-analysis of 229 studies covering over 10M patients

Abstract: Background: This review aims to investigate the association of sex with the risk of multiple COVID-19 health outcomes, ranging from infection to death. Methods: Pubmed and Embase were searched through September 2020. We considered studies reporting sex and coronavirus disease 2019 (COVID-19) outcomes. Qualitative and quantitative data were extracted using standardised electronic data extraction forms with the assessment of Newcastle Ottawa Scale for risk of bias. Pooled trends in infection, hospitalization, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…We observed a sex difference in the relationship between critical illness and subsequent risk of diabetes incidence among postdischarge COVID-19 patients. Current evidence suggests that men have a higher risk of COVID-19 infection, hospitalization, disease severity, ICU admission, and death than women [ 31 ], which may partly support our result about sex differences. Though the mechanism was unclear, genetic/epigenetic factors, sex differences in the immune response [ 32 , 33 ], androgens-mediated ACE2 expression [ 34 , 35 ], and gut microbiome-mediated immune modulation [ 36 ] may be reasons for sex-based differences.…”
Section: Discussionsupporting
confidence: 81%
“…We observed a sex difference in the relationship between critical illness and subsequent risk of diabetes incidence among postdischarge COVID-19 patients. Current evidence suggests that men have a higher risk of COVID-19 infection, hospitalization, disease severity, ICU admission, and death than women [ 31 ], which may partly support our result about sex differences. Though the mechanism was unclear, genetic/epigenetic factors, sex differences in the immune response [ 32 , 33 ], androgens-mediated ACE2 expression [ 34 , 35 ], and gut microbiome-mediated immune modulation [ 36 ] may be reasons for sex-based differences.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the sampled population is heterogeneous in terms, for instance, of age and sex. Indeed, despite the limited number of patients, we found an association between neurological and severe respiratory symptoms and between symptom severity in general, and age and sex, as reported in the literature [ 42 , 60 ]. Thus, the reported results are worth of attention and deserve further validation in larger cohorts of patients.…”
Section: Discussionsupporting
confidence: 73%
“…This difference might be the result of factors (eg, smoking status, obesity, and comorbidities) more common in male comparators that also increased the risk of severe disease; alternatively, the proportion of men in our cohort was smaller, so our study might have lacked power to detect differences. 21 , 23 Indeed, a study by England and colleagues 7 using the US Veterans Affairs rheumatoid arthritis cohort, which is enriched for men, also examined the risk of COVID-19 hospitalisation or death among patients with rheumatoid arthritis versus patients without rheumatoid arthritis from the Veterans Affairs system. They found that rheumatoid arthritis was associated with a 35% higher risk, especially among those patients with rheumatoid arthritis using DMARDs or glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%